Bactericidal and biofilm eradication efficacy of a fluorinated benzimidazole derivative, TFBZ, against methicillin-resistant Staphylococcus aureus - Chen, Qian; Dong, Zhihui; Yao, Xuedi; Sun, Huan; Pan, Xin; Liu, Jikai; Huang, Rong (Frontiers in Pharmacology, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major inducement of nosocomial infections and its biofilm formation render the high tolerance to conventional antibiotics, which highlights the requirement to develop new antimicrobial agents urgently. In this study, we identified a fluorinated benzimidazole derivative, TFBZ, with potent antibacterial efficacy toward planktonic MRSA (MIC=4 μg/mL, MBC=8 μg/mL) and its persistent biofilms (≥99%, MBEC = 8 μg/mL). TFBZ manifested significant irreversible time-dependent killing against MRSA as characterized by diminished cell viability, bacterial morphological change and protein leakage. Furthermore, the results from CBD devices, crystal violet assay in conjunction with live/dead staining and scanning electron microscopy confirmed that TFBZ was capable of eradicating preformed MRSA biofilms with high efficiency. Simultaneously, TFBZ reduced the bacterial invasiveness and exerted negligible hemolysis and cytotoxicity toward mammalian cells, which ensuring the robust therapeutic effect on mouse skin abscess model. The transcriptome profiling and quantitative RT-PCR revealed that a set of encoding genes associated with cell adhesion, biofilm formation, translation process, cell wall biosynthesis was consistently down-regulated in MRSA biofilms upon exposure to TFBZ. In conclusion, TFBZ holds promise as a valuable candidate for therapeutic applications against MRSA chronic infections.